The hippocampus and memory: insights from spatial processing - Bird, Chris M.; Burgess, Neil (Nature reviews. Neuroscience, 2008)
Key Points Damage to the hippocampus in humans can cause profound impairments in long-term episodic memory, but the precise functional contribution of the hippocampus remains the subject of several competing theories. Electrophysiological studies in rodents have characterized the firing properties of 'place cells' in the hippocampus in great detail. Place cells appear to represent where an animal 'thinks' it is located in an environment, relative to environmental boundaries. Acting cooperatively, place cells encode specific environments, performing both pattern completion and pattern separation. A new model of hippocampal processing that is driven by the properties of place cells (the BBB model) provides an alternative to existing psychological theories, at least in the spatial domain. The BBB model proposes that the hippocampus is needed to impose a location from which to retrieve and construct a coherent mental image of an environment. This mental image supports the online maintenance and manipulation of representations of the locations of objects and features in an environment. The model suggests that episodic memory will always be hippocampus-dependent if it is associated with rich mental imagery of an environment. Other sophisticated long-term spatial (and non-spatial) representations can be acquired, stored and retrieved independent of the hippocampus. However, the hippocampus is often needed to mediate behaviours that allow such learning to take place (such as when learning a new route). The BBB model further suggests that the hippocampus is required for both short-term and long-term memory for some types of information, for imagining complex visual scenes (be they real or fictitious), and more for the recognition of scenes than faces. Recent experimental evidence from studies of the effects of damage to the hippocampus in humans supports all three of these proposals. Hippocampal processing beyond the spatial domain cannot be explained by the BBB model, but several theoretical positions have been advanced to address the broader role of the hippocampus in mnemonic processing. Bird and Burgess review the hippocampus's role in memory in light of a model of neuronal processing in which hippocampal activity constrains neocortical information to be perceivable from a single location. This enables spatially coherent mental imagery, explaining several recent findings and theoretical conflicts. The hippocampus appears to be crucial for long-term episodic memory, yet its precise role remains elusive. Electrophysiological studies in rodents offer a useful starting point for developing models of hippocampal processing in the spatial domain. Here we review one such model that points to an essential role for the hippocampus in the construction of mental images. We explain how this neural-level mechanistic account addresses some of the current controversies in the field, such as the role of the hippocampus in imagery and short-term memory, and discuss its broader implications for the neural bases of episodic memory.